THE EFFECT OF FINANCIAL MANAGEMENT, FINANCIAL TECHNOLOGY, AND SOCIAL CAPITAL ON MSME PERFORMANCE IN WEST JAKARTA CITY - Agus Saputra; Mohamad Trio Febriyantoro; Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Jurnal Akuntansi dan Manajemen Bisnis, 2022)
Several factors affect the performance of MSMEs, including internal and external factors. The problems faced by MSMEs are related to weak financial management, financial technology, and social capital. These three variables attract the attention of current research and the results of previous studies have not been consistent. This study aims to analyze the effect of financial management, financial technology, and social capital on the performance of MSMEs in West Jakarta. The research population is 108 respondents. The sampling technique uses an online questionnaire. This research is a quantitative research with analysis using SPSS. The research results obtained a significant effect between financial management and social capital on the performance of MSMEs. But the financial technology variable has an effect and is not significant on the performance of MSMEs.